Performance of lambs fed with macauba pie inclusion in the diet - Azevedo, Rafael Alves de; Rufino, Luana Marta de Almeida; Santos, Antonio Carlos Ramos dos; Silva, Lígia Pires da; Bonfá, Hugo Colombarolli; Duarte, Eduardo Robson; Geraseev, Luciana Castro (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the nutrient uptake and the productive and economic performance of confined Santa Inês lambs fed diets with different levels of macauba pie inclusion . The animals (24) were distributed in a randomized block design, in treatments with 0, 100, 200 and 300 g kg-1 macauba pie in the diet dry matter, with six replicates during 60 days of confinement. The addition of macauba pie at increasing rates to the diet linearly increased the intake of crude protein, ether extract, neutral detergent fiber and feed conversion. There was no difference in dry matter intake, average daily gain and total live weight gain with the macauba pie addition. Diet with 100 g kg-1 macauba pie inclusion showed the best cost:benefit ratio in the evaluation of gross and net revenues from the sale of live and slaughtered animals. The addition of macauba pie up to 300 g kg-1 to the diet does not affect the animal growth performance; however, the addition of 100 g kg-1 macauba pie provides a better economic return.
Keywords: Acrocomia aculeata; feedlot; by‑product; sheep; termination